Lived Experiences, Challenges Encountered, And Coping Mechanisms of Grade 7 Students from Single-Parent Families: Basis for Counseling Program - Amontos, Fermin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences, challenges, and coping mechanisms of Grade 7 students from single-parent families at Usab High School in the City of Masbate during School Year 2025–2026 and served as the basis for a proposed counseling program. Guided by a systems approach involving input, process, output, and feedback, the study employed a qualitative phenomenological design. Fifteen students who had lived in single-parent households for at least one year were selected through purposive sampling. Data were collected through expert-reviewed, semi-structured face-to-face interviews, audio-recorded with consent, transcribed verbatim, validated through member checking, and analyzed using thematic analysis. The findings revealed that the students assumed household responsibilities at an early age, developed resilience and independence, experienced emotional struggles related to parental absence, valued family support, and faced financial and social difficulties. Their major challenges included bullying and social exclusion, loneliness and emotional distress, limited financial resources, reduced parental participation in school activities, and difficulty balancing household and academic responsibilities. They coped through emotional release and self-soothing activities, faith and prayer, support from family members and significant others, emotional maturity, perseverance, and commitment to education. The study concluded that these learners experience significant emotional, social, financial, and academic difficulties but demonstrate resilience through personal strengths and available support systems. It recommends strengthening inclusive classroom practices, guidance and counseling services, anti-bullying initiatives, parental involvement, peer support, and the proposed counseling intervention program. The study supports SDG 4 on Quality Education and SDG 3 on Good Health and Well-Being by promoting inclusive education and psychosocial support for vulnerable learners. Its sustainability impact lies in strengthening educational, social, and institutional support systems that promote student well-being and continued participation in education.
Keywords: Academic Resilience; Coping Mechanisms; Lived Experiences; School Counseling; Single-Parent Families; Social Support; Student Well-Being